2020
DOI: 10.1111/ans.16315
|View full text |Cite
|
Sign up to set email alerts
|

B3 lesion upgrade rates in a tertiary Australian breast centre: a 8‐year experience (2012–2019)

Abstract: Background: B3 breast lesions identified on core needle biopsy have uncertain malignant potential. Traditional management of these lesions has been surgical excision, but there is growing interest in less invasive and more cost-effective alternatives such as vacuumassisted excisional biopsy (VAEB). Determining the rate of malignant upgrade for B3 lesions is important as it may identify low-risk lesions where VAEB could be considered. Methods: A retrospective study was conducted of women undergoing an elective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(117 reference statements)
2
6
0
Order By: Relevance
“…Mayer et al found that the upgrade rate of B3b lesions by biopsy was higher, and it was more meaningful to perform surgery ( 18 ). Our results are consistent with previous reports that the likelihood of upgrade in HR-II was significantly reduced ( 17 - 19 ), suggesting that the evaluation of AH components could be useful in guiding the follow-up management of HRLs. Because the upgrade rates of HR-I and HR-II are very different, it is important to select the correct follow-up management.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mayer et al found that the upgrade rate of B3b lesions by biopsy was higher, and it was more meaningful to perform surgery ( 18 ). Our results are consistent with previous reports that the likelihood of upgrade in HR-II was significantly reduced ( 17 - 19 ), suggesting that the evaluation of AH components could be useful in guiding the follow-up management of HRLs. Because the upgrade rates of HR-I and HR-II are very different, it is important to select the correct follow-up management.…”
Section: Discussionsupporting
confidence: 92%
“…Second, we added features of breast parenchyma and found that BPE was an independent factor in predicting upgrade. Third, previous studies have proved that HRLs with AH are more likely to upgrade (17)(18)(19). To better determine the need for surgery, we further analyzed the factors that predicted the upgrade of HR-I and HR-II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the overall upgrade rate to malignancy for B3 lesions was 26.4% for BreastScreen NSW, Australia. This is consistent with the upgrade rates reported in the literature which ranged from 10 to 35% [ [ 6 , [11] , [12] , [13] , [14] ]]. The majority of the B3 lesions were upgraded to DCIS (69.2%) instead of invasive cancers (29.6%) and a much smaller proportion to malignant phyllodes (1.0%), similar to results in the literature [ [ 11 , 12 , 14 ]].…”
Section: Discussionsupporting
confidence: 91%
“…The B 5-tier classification for breast lesions is used to categorize core biopsy histological results [1] . Lesions of uncertain malignant potential (“B3” category) are a heterogeneous group, with upgrades to malignancy ranging from <2% to almost 40% [2] .…”
Section: Introductionmentioning
confidence: 99%